MENGULIK FAKTOR-FAKTOR PENYEBAB PASIEN GANGGUAN JIWA DI YAYASAN VILLA PEMULIHAN PELITA (Institut Agama Kristen Negeri Manado, 2023)
Mental disorders are a serious problem in this world, because mental disorders can prevent someone who experiences them from carrying out actions in social society. Even though there is modern understanding and treatment of mental disorders, there are still many people and even Christians who associate mental disorders with possession by evil spirits. This can trigger stigma towards people suffering from mental disorders and hinder their access to appropriate medical care. Article 3 of the Republic of Indonesia Constitution Number 18 of 2014 reads